2011
DOI: 10.1007/s10646-011-0645-x
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl radical generation and oxidative stress in earthworms (Eisenia fetida) exposed to decabromodiphenyl ether (BDE-209)

Abstract: Antioxidant responses induced by decabromodiphenyl ether (BDE-209) in the earthworms (Eisenia fetida) were studied after 7 days of exposure. Electron paramagnetic resonance (EPR) spectra indicated that hydroxyl radicals (•OH) in earthworms were significantly induced by 0.01-10 mg/kg of BDE-209. Malondialdehyde (MDA) and protein carbonyl (PCO) were stimulated at 0.5-10 mg/kg and 1-10 mg/kg, respectively. The reduced glutathione (GSH) was inhibited at 1-10 mg/kg while oxidized glutathione (GSSG) accumulated at 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 34 publications
(31 reference statements)
5
14
0
Order By: Relevance
“…Researches suggest that reactive oxygen species (ROS), can be induced in organisms exposed to some environmental contaminants [4][5][6]. Recent study suggested that Roundup® might induce oxidative stress in aquatic organisms through the increased levels of tissue lipid hydroperoxides [7].…”
Section: Introductionmentioning
confidence: 99%
“…Researches suggest that reactive oxygen species (ROS), can be induced in organisms exposed to some environmental contaminants [4][5][6]. Recent study suggested that Roundup® might induce oxidative stress in aquatic organisms through the increased levels of tissue lipid hydroperoxides [7].…”
Section: Introductionmentioning
confidence: 99%
“…Earthworm (E. fetida) is an attractive biological model because it is available commercially, easy to handle, susceptible to chemicals, and can be bred readily in a wide range of organic waste materials (Organisation for Economic Co-operation and Development (OECD) 1984). Mortality and growth inhibition of earthworms (E. fetida) have been verified as effective indicators in a variety of reports (Shi et al 2007;Wu et al 2011;Xie et al 2011). As a sensitive indicator, gene transcript level has been used in assessing toxic effects of toxicants to earthworms (E. fetida) (Asensio et al 2007;Brulle et al 2007Brulle et al , 2008Zheng et al 2008).…”
mentioning
confidence: 99%
“…Biochemical responses of earthworms (E. fetida) to some congeners of PBDEs have been reported. Antioxidant responses induced by decabromodiphenyl ether (BDE-209) have been reported in earthworms (E. fetida) (Xie et al 2011). Activities of superoxide dismutase (SOD), CAT, and peroxidase were measured to study the toxic effects of 2,3 0 ,4 0 ,6-tetrabromodiphenyl ether (BDE-71) in earthworms (E. fetida) (Zhu et al 2010).…”
mentioning
confidence: 99%
“…Oxidative stress is generated by the excessive reactive oxygen species (ROS) in living organisms, caused by exposure to heavy metals and organic contaminants (Saint-Denis et al, 2001;Lin et al, 2010). Oxidative stress was produced in earthworms exposed to BDE 209, HBCD and TBBPA by the generation of excessive hydroxyl radical ROS (Xue et al, 2009;Jin et al, 2010;Marvin et al, 2011;Xie et al, 2011;Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has detected that the gene expression of antioxidant enzymes and Hsp70 in earthworms is involved in the oxidative stress responses to heavy metals (Homa et al, 2007;Brulle et al, 2010;Xiong et al, 2014) and organic chemicals (Chen et al, 2011a,b). Reports indicated that BDE 209 and TBBPA induced the ROS and activities of selected antioxidant enzymes in earthworms (Xue et al, 2009;Xie et al, 2011;Zhang et al, 2014), however, little is known about the transcriptional regulation of antioxidant and stressresponse gene at the mRNA level with respect to the response of earthworms to HBCD, BDE 209 and TBBPA, and warrant more thorough investigation.…”
Section: Introductionmentioning
confidence: 99%